2010
DOI: 10.5539/ibr.v3n3p187
|View full text |Cite
|
Sign up to set email alerts
|

Issues on Takaful Affecting the Choice of Accounting Policies: A Case Study of Two Takaful Companies in Malaysia

Abstract: The paper adopts a descriptive case study method to examine the impact of juristic views on the operations of two Malaysian takaful companies. In order to achieve this objective, the annual financial reports of both companies were analysed. Interviews with each company's finance managers and with a member of the Malaysian Shariah Advisory Council were undertaken for a more in-depth coverage. Also a written correspondence with a senior official of the central bank was accomplished. Similarities and differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Another issue of focus was about the operational models of agency and investment. These models have been criticised and blamed for all inconsistences and considered as wrong basis of establishing Islamic insurance contracts (Alpen Capital, 2010;Annuar & Abu Bakar, 2010;Standard & Poor's Financial Services LLC, 2011;Best, 2013). Likewise, Olorogun (2013b) evaluated the diffusion of agency theory into Islamic insurance agency operational model and found that the agency contract was just a claim.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another issue of focus was about the operational models of agency and investment. These models have been criticised and blamed for all inconsistences and considered as wrong basis of establishing Islamic insurance contracts (Alpen Capital, 2010;Annuar & Abu Bakar, 2010;Standard & Poor's Financial Services LLC, 2011;Best, 2013). Likewise, Olorogun (2013b) evaluated the diffusion of agency theory into Islamic insurance agency operational model and found that the agency contract was just a claim.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tenacious criticisms from the markets' reporters about the Islamic insurance industry practices and regulation disparities across regions were common. Even Annuar and Abu Bakar (2010) found disparity of accounting and auditing policies among Islamic insurance companies in Malaysia. It is clear at this point that Islamic insurance proponents have asserted many efforts; nevertheless, it is not enough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alpen Capital, Middle East Insurance Review (MEIR), The World Takaful Report (WTR) and Islamic Finance News (IFN). For the sake of brevity, the information are more detailed in these business and academic magazines, thus for more details kindly refer to Alpen Capital ( mudharabah (Billah, 2003;Maysamia, & Williams 2006;Abdul Wahab, Lewis & Hassan, 2007;Al-Qurradaghi, 2009;Al-Shubayli, 2009;Abdul Kader, Adams, & Hardwick 2010;Annuar & Abu Bakar 2010;Khan, et al 2011). The recent enactment aimed to eliminate or minimise excesses in the process of making and arriving at legal rulings on Islamic finance products (Malaysian Government 2013).…”
Section: Introductionmentioning
confidence: 98%